Greenhouse Gas Emissions in the Everglades: The Role of Hydrologic Conditions - Alan L. Wright; K. Ramesh Reddy (EDIS)
SL288, a 5-page illustrated fact sheet by Alan L. Wright and K. R. Reddy, describes the relationship between global warming and increases in greenhouse gas emissions, the role of Everglades wetlands in the global carbon cycle and their contribution to greenhouse gas production, and how hydrologic conditions and eutrophication in the Everglades influence the rates and types of greenhouse gases emitted. Includes references. Published by the UF Department of Soil and Water Science, May 2009.